2004
DOI: 10.1016/j.seizure.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A study on awareness and attitude of teachers on epilepsy in Istanbul

Abstract: Epilepsy is a disease frequently seen among school children. Children having seizures may bother their teachers, who do not receive specific training about epilepsy during their education. Moreover, teachers feel desperate not knowing how to handle the situation. In a series of seminars it was our aim both to investigate and to improve the present awareness, knowledge, and attitude of elementary school teachers about epilepsy in Istanbul. In the pre- and post-seminar tests teachers who attended the seminar on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 11 publications
6
44
1
1
Order By: Relevance
“…Considerable attention has been paid to determination of factors influencing knowledge of and attitudes towards epilepsy among teachers. It was reported that more experienced teachers [28] and/ or the teachers who received pre-service or in-service epilepsy training [29] have more favorable attitudes and greater epilepsy-related knowledge. Our recent study shows that teachers having a personal experience with epilepsy exhibit a significantly higher level of knowledge and more positive attitudes towards people with epilepsy compared with teachers not having this experience [30] .…”
Section: Knowledge Of Familiarity With and Attitudes Towards Epilepsmentioning
confidence: 99%
“…Considerable attention has been paid to determination of factors influencing knowledge of and attitudes towards epilepsy among teachers. It was reported that more experienced teachers [28] and/ or the teachers who received pre-service or in-service epilepsy training [29] have more favorable attitudes and greater epilepsy-related knowledge. Our recent study shows that teachers having a personal experience with epilepsy exhibit a significantly higher level of knowledge and more positive attitudes towards people with epilepsy compared with teachers not having this experience [30] .…”
Section: Knowledge Of Familiarity With and Attitudes Towards Epilepsmentioning
confidence: 99%
“…A necessity to call for help was reported by 43.7% before and 50.9% after the program. Another example of a good training outcome was presented by Bekiroğlu et al (2004), this time teachers of primary schools from Istanbul participated. Before the training 69.3% of the group heard or read about epilepsy, 59.4% knew a person with epilepsy.…”
Section: Turkeymentioning
confidence: 99%
“…In 2004 done "A study on awareness and attitude of teachers on epilepsy in Istanbul" the study done among 346 teachers, and it was showed that more than half of teachers heard about epilepsy, while 71.9% attended seizure attack, and 59.4% knew someone with epilepsy. There was some misconceptions like 2.3% think epilepsy is contagious, or a psychological disease 17.8% 16 .…”
Section: Introduction:-mentioning
confidence: 99%